Evaluation of physalis phytomass (Physalis peruviana L.) - Muniz J.* (2014)
Physalis peruviana L. is a plant of Andean origin (its fruit is also known as the Cape gooseberry), with high potential for cultivation in Brazil. The aim of this study was to evaluate the accumulation of fresh and dry matter of physalis plants on three training systems. Experiments were carried out in the field, in the city of Lages, Santa Catarina, Brazil, in 2008/2009. The experimental design was randomized blocks with 2 x 3 factorial arrangements. The training systems tested were a vertical-shoot positioned trellis, an 'X' system and a 'V' system. Two planting densities were used: 3.00 m x 0.50 m and 3.00 x 1.00 m. Variables recorded were fresh matter, dry matter, number of leaves, flower buds, flowers and fruits, and fresh and dry matter of roots. Plants on the vertical-shoot positioned trellis, at both planting densities, showed 39% more fresh matter than plants on system X and 64% more than plants on system V. With respect to dry matter, the system on the vertical-shoot positioned trellis, at both planting densities, was superior. Results recorded for system X, planting density 3.00 x 0.50 m, were similar. With respect to fresh and dry matter of roots, the vertical-shoot positioned trellis was superior. It was concluded that physalis plants on a verticalshoot position trellis gave more fresh matter, a higher number of fruits and higher productivity. An increase in planting density did not lead to a significant increase in the mass of fresh or dry matter of the plants. Physalis peruviana plants, at conditions of southern Brazil, present 3,518.37 g of the aerial fresh matter, 851.72 g of the aerial dry matter, 269.93 g of the root fresh matter and 84.38 g of root dry matter.